2020
DOI: 10.3390/molecules25245820
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Homo- and Heterodimers of Natural Enkephalinase Inhibitors in Experimental Colitis in Mice

Abstract: Background: the pharmacological treatment and/or maintenance of remission in inflammatory bowel diseases (IBDs) is currently one of the biggest challenges in the field of gastroenterology. Method: our aim was the synthesis of homo- and heterodimers of natural enkephalinase inhibitors (opiorphin; sialorphin; spinorphin) and the in vitro characterization of their effect on the degradation of enkephalin by neutral endopeptidase (NEP) and stability in human plasma. We investigated the in vivo heterodimer of Cys co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Sobocińska et al 7 (2020) studied the effects of sialorphin and spinorphin on a mouse model of colitis and suggested these peptides as anti-inflammatory elements.…”
Section: Discussionmentioning
confidence: 99%
“…Sobocińska et al 7 (2020) studied the effects of sialorphin and spinorphin on a mouse model of colitis and suggested these peptides as anti-inflammatory elements.…”
Section: Discussionmentioning
confidence: 99%
“…NEP inhibitors, thiorphan and acetorphan, are identified to exert anti-diarrheal activity in rodents via the protection of endogenous enkephalins ( Marҫais-Collado et al, 1987 ; Sałaga et al, 2013 ). Recent studies show that a natural inhibitor of NEP/APN, sialorphin, attenuates TNBS-induced colitis in mice ( Sałaga et al, 2017 ; Sobocińska et al, 2020 ). Similarly, our results revealed that i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our data demonstrated that HO attenuates DSS-induced colitis by blocking NEP and APN through activation of the endogenous enkephalin-dependent opioid pathway. However, a recent study reports that systemic administration of human opiorphin has no effect on TNBS-induced colitis in mice ( Sobocińska et al, 2020 ). Although inflammatory pathways induced by DSS and TNBS in experimental models of colitis in mice are similar, DSS-induced ulcerative colitis is more severe than TNBS-induced colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was reflected in the first edition of the Special Issue Advances in Research of Short Peptides . The issue received a large number of truly impressive and gratifying contributions, each of which reveals still open problems or challenges [ 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]; therefore, it seems advisable to the Editors to extend a follow-up collection of articles providing the newest results of research on short peptides with a more flexible approach worth being further developed toward applications in bio-medicine. As we move forward to new advances and look back on the studies on short peptides, the aim remains the same—reaching their full potential.…”
mentioning
confidence: 99%